Life history aspects of the mayfly Siphlonurus typicus (Ephemeroptera: Siphlonuridae) with a new application for measuring nymphal development and growth - Kosnicki, E.; Burian, S. (Hydrobiologia, 2003)
Little is known about the life history of mayflies that inhabit temporary ponds. The purpose of this study was to observe and quantify life histories attributes of Siphlonurus typicus, which is known to reside in temporary ponds. Weekly samples of nymphs were taken from two temporary ponds in eastern Connecticut from March to June, 1999. Individuals were graded into 11 maturity classes, based on developmental characteristics, as a means of predicting population maturity rates. Head capsule widths (HCWs) were used to determine if growth occurred between maturity classes. Degree days were found to be an excellent predictor for population maturity (r2 = 0.963, p < 0.0001). Nymphs that hatched earlier in the year had larger HCWs than nymphs that hatched later in the year, possibly because of different temperature regimes. The University of Connecticut Forest pond (UCF) population matured faster than the Merrow Meadows pond (MER) population, but both sexes of the UCF population tended to be smaller than their counter parts from the MER population. Sex ratios were female bias for the UCF population (1.35:1), but were not different for the MER population. Adult emergence and mating occurred from 27 May to 21 June. There was a positive relationship between number of eggs per female and female body length. Oviposition at both sites occurred directly on the ponds, pond inlets, and outlets, indicating that pond populations were the result of local migrants as well as permanent residents. Temperature was a determining factor of maturity and fecundity for Siphlonurus typicus.
Keywords: Age classes; Arthropoda; Biodiversity; Ephemeroptera; Growth rates; Invertebrata; Marine biology; Mating behavior; Maturity; Maturity rates; Mayflies; Ponds; Population statistics; Siphlonuridae; Siphlonurus; Siphlonurus typicus; Swarming; dept.bio; ephemeral pool; growth; larval development; life history; mayfly; swarming

Life stage descriptions, taxonomic notes, and new records for the mayfly family Leptohyphidae (Ephemeroptera) - Baumgardner, David E.; Burian, Steven K.; Bass, David (Zootaxa, 2003)
Keywords: dept.bio